The Impact of Role Play on Enhancing Learners’ Interaction in Speaking - Lahbibi, Khalid; Farhane, Hamza (International Journal of Language and Literary Studies, 2023)
This practical action research assesses the impact of using role play in developing Moroccan high school students’ English speaking skills. Role play is one way where students can use English in a real life context, and thus they end up improving their English speaking skills or at least transferring the knowledge they are taught to a real life situation. A lot of Moroccan high school English teachers have recently noticed that their students’ English speaking is not really good, and they have then started conducting action research based on different teaching strategies that can be used to help students improve their English speaking skills. We conduct an experiment where we divide students into two groups: a control group (n:20) which is taught without using role play, and the experimental group (n:20) which is taught using role play. The results report role play to have a positive effect on students’ speaking skills in the sense that there is a significant difference in the mean score between the control group and the experimental group.